2016
DOI: 10.1021/acs.est.6b03284
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Duty Diesel Exhaust Particles during Engine Motoring Formed by Lube Oil Consumption

Abstract: This study reports high numbers of exhaust emissions particles during engine motoring. Such particles were observed in the exhaust of two heavy duty vehicles with no diesel particle filter (DPF), driven on speed ramp tests and transient cycles. A significant fraction of these particles was nonvolatile in nature. The number-weighted size distribution peak was below 10 nm when a thermodenuder was used to remove semivolatile material, growing up to 40 nm after semivolatile species condensation. These particles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Generic speciation of compounds in diesel exhaust, diesel fuel and lubricating oil provides the basis for such a conclusion [51,52]. Other such apportionment estimates have been reported [28,53,54], and between diesel and gasoline emissions [37].…”
Section: (V) Chemical Reactionmentioning
confidence: 95%
See 1 more Smart Citation
“…Generic speciation of compounds in diesel exhaust, diesel fuel and lubricating oil provides the basis for such a conclusion [51,52]. Other such apportionment estimates have been reported [28,53,54], and between diesel and gasoline emissions [37].…”
Section: (V) Chemical Reactionmentioning
confidence: 95%
“…This leads to particle shrinkage and a change in particle composition for multi-component particles, but not a change in number concentration [24,25], unless particles evaporate fully. Heating diesel particles shows a substantial volatile fraction [26][27][28].…”
Section: (Iv) Evaporationmentioning
confidence: 99%
“…Field and laboratory experiments have demonstrated that the presence and properties of nucleation mode particles in vehicle emissions depend on multiple factors, including the vehicle engine and emission after-treatment technologies, driving conditions, used fuels and lubricant oils, and ambient meteorological conditions (e.g. Lee et al 2015, Karjalainen et al 2016b, 2016c, Saliba et al 2017, Timonen et al 2017. A further complication arises from the observations that the nucleation mode particles associated with motor vehicle emissions may contain a non-volatile core (Sgro et al 2008, Lähde et al 2009.…”
Section: Npf Associated With Transportationmentioning
confidence: 99%
“…Hydrocarbon concentrations are not limited to vehicle exhaust systems but can occur in the entire vehicle fuel system from vapors during dispensing and distribution of fuel, which accounts for 15-20%, with the crankcase providing 20-30%. However, diesel exhaust remains the main culprit in engine emissions accounting for 50-60% of all the UHC concentration [66,67]. Figure 16 shows the variation of UHC emission with engine speed in the stationary diesel power generator using blends of biodiesel.…”
Section: Unburnt Hydrocarbon (Uhc) Concentrationmentioning
confidence: 99%